Optimized Performance of Consensus algorithm in Multi Agent System Using PSO - Raafat, Safanah Mudheher; Hasan, Ahmed Mudheher; Khairi, Teaba Wala Aldeen; Ali, Karar Ghalib (Al-Nahrain Journal for Engineering Sciences, 2018)
This paper provides a theoretical framework for analysis of consensus algorithm for multi-agent networked systems considering the role of directed information flow. Improvement of the performance of the implemented consensus algorithm has been achieved by using Particle Swarm Optimization (PSO). Concepts of information consensus in networks and methods of convergence are applied as well. Our analysis framework is based on tools algebraic Graph Theory (GT). Simulation of multi-agent system and the performance of a consensus algorithm have been discussed. Acceleration the network while approaching the required goal has been accomplished and elimination of undesired swing that appears during the acceleration was proved.